The influence of the integration of local knowledge during chemistry hands-on practical activities on grade 8/9 learners' attitude towards science - Ngqinambi, Akhona (Rhodes University, Faculty of Science, Department of Chemistry, 2020)
With every passing year, there is a decrease in the number of learners pursuing science degrees after completion of grade 12. One of the main reasons for this is the negative attitude that high school learners have towards science learning and science as an entity. The Natural Sciences curriculum suggests the use of local knowledge to introduce the usefulness and the relatability of science to learners. This study is an intervention that seeks to ascertain the influence that local knowledge has on the attitudes of grade 8/9 learners when integrated into their chemistry hands-on practical activities. The study was informed by Vygotsky's social constructivist theory and Wenger's community of practice theory. Grade 8/9 learners from four high school science clubs did three local knowledge integrated experiments based on acids and bases. The learners completed pre- and post- surveys and were interviewed about their experiences. Volunteers at the science clubs were also interviewed. Excel was used to deductively analyse quantitative data. On the other hand, an inductive-deductive thematic approach was used to analyse the qualitative data. The findings of the study showed a divergence of qualitative and quantitative methods. The quantitative data showed that there was a slight decrease (but not statistically significant) in the attitude of the learners after engaging in chemistry hands-on practical activities into which local knowledge had been integrated. On the other hand, the qualitative data showed that there was a positive shift in the learners' attitudes after they had been engaged in the chemistry hands-on practical activities. Additionally, the findings of the study revealed that the integration of local knowledge promotes conceptual understanding and improves the performance of the learners. This study thus recommends that local knowledge should be integrated into the grade 8 and 9 learners' curriculum to enrich and promote contextualized science for learners. Additionally, the integration of local knowledge would promote conceptual understanding and spark interest and motivation in learners to pursue science-related careers.
Keywords: Science -- Study and teaching (Secondary) -- South Africa; Science teachers -- South Africa; High school students -- Attitudes; Communities of practice -- South Africa; Science clubs -- South Africa; Science projects -- South Africa; Constructivism (Education) -- South Africa; Educational counseling -- South Africa; Local knowledge